Respuesta :
Answer:
-64
Step-by-step explanation:
a(b - c)
a = -8
b = 12
c = 4
So, you'd plug in those numbers:
-8(12 - 4)
You'd start within the parenthesis's, so:
(12 - 4), which equals (8)
-8(8)
= -64
Hey there!
[tex]\large\text{a(b - c)}[/tex]
[tex]\large\text{= -8(12 - 4)}[/tex]
[tex]\large\text{12 - 4 = \bf 12}[/tex]
[tex]\large\text{= -8(12)}[/tex]
[tex]\large\textsf{ = \bf -64}[/tex]
[tex]\huge\boxed{\textsf{Therefore, your answer is: -64}}\huge\checkmark[/tex]
[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]
~[tex]\frak{Amphitrite1040:)}[/tex]